2004
DOI: 10.1167/iovs.03-0693
|View full text |Cite
|
Sign up to set email alerts
|

Energy Substrate Requirements of Rat Retinal Pigmented Epithelial Cells in Culture: Relative Importance of Glucose, Amino Acids, and Monocarboxylates

Abstract: Rat RPE cells require glucose as their primary metabolic substrate in culture, but can metabolize glutamine in its absence. When glucose and glutamine are limiting, RPE cells can metabolize monocarboxylates such as lactate or pyruvate. These data provide evidence that such cells are able to withstand various types of insult brought about by nutrient deprivation, by altering their pathways of energy production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 50 publications
2
19
0
Order By: Relevance
“…when monocarboxylate transfer into the oocyte or mitochondria was inhibited with 4-CIN, oocyte activation increased to the highest level in the presence of either pyruvate, lactate, or glucose. This suggested that as in other cell types [67,68], transportation of lactate and pyruvate across the plasma membrane and into mitochondria was also dependent on the MCTs in the aging oocyte. Furthermore, the present study showed that unlike lactate, pyruvate did not rely solely on electron transport for its inhibition of oocyte aging.…”
Section: Discussionmentioning
confidence: 78%
“…when monocarboxylate transfer into the oocyte or mitochondria was inhibited with 4-CIN, oocyte activation increased to the highest level in the presence of either pyruvate, lactate, or glucose. This suggested that as in other cell types [67,68], transportation of lactate and pyruvate across the plasma membrane and into mitochondria was also dependent on the MCTs in the aging oocyte. Furthermore, the present study showed that unlike lactate, pyruvate did not rely solely on electron transport for its inhibition of oocyte aging.…”
Section: Discussionmentioning
confidence: 78%
“…Rat retinal cell cultures comprising both neurons and glia were prepared using a trypsin-mechanical digest procedure previously described. 17,18 Briefly, retinas were enucleated from 1-to 2-day-old rat pups and incubated in physiological buffer (solution medium; 120 mM NaCl, 5.4 mM KCl, 24 mM NaHCO 3 , 0.1 mM NaH 2 PO 4 , 3 g/L BSA, 20 mM glucose, and 0.15 mM MgSO 4 , 28 lM phenol red) containing 0.1 mg/mL trypsin (Sigma-Aldrich) at 378C for 8 minutes. After the reaction was stopped, cells were resuspended in minimal essential medium (MEM) containing 10% FBS, 10 mg/mL gentamicin sulfate, 200 lM glutamine, and 25 mM glucose and applied to 13-mm-diameter borosilicate glass coverslips (immunocytochemistry), 6-well plates (Western blot), or 12-well plates (ATP assay and reactive oxygen species determination), all of which had previously been coated with 10 lg/mL poly-D-lysine, for 2 hours.…”
Section: Rat Retinal Cell Culturesmentioning
confidence: 99%
“…MTT is reduced to an insoluble, blue formazan product because of acceptance of electrons from cellular reducing equivalents such as NADH, NADPH, or succinate, thus providing an assay for the REDOX state of a sample. 36 The REDOX potential is a measure of the oxidative status of a cell-a fall in the potential implies that the balance is in favour of oxidation, as might arise through the action of ROI. WST-1 (4-[3-(4-iodophenyl)-2-(4-nitrophenyl)-2H-5-tetrazolio]-1,3-benzene disulfonate) is a tetrazolium dye containing an electron coupling agent that is cleaved by mitochondrial dehydrogenases to a formazan dye with an absorbance at 490 nm (Roche, USA).…”
Section: Preliminary Studies In Support Of the Hypothesis (Figs 2 And 3)mentioning
confidence: 99%